Contradictions of inclusion and spectacularization of Calipso Limonense in Costa Rican hegemonic culture. Notes for possibles frameworks of analysis - Navarro Alvarado, Guillermo (2015)
The following article aims to problematize the socio-cultural and socio-historical processes that mark the insertion of Calypso Limonense as peripheral culture into ideological structures of the nation state and the Costa Rican hegemonic culture. The first two sections of the article made a general characterization of the dynamics of accumulation, racism and marginalization of Caribbean social space where calypso arises. The third, fourth and fifth sections are used to analyze the contradictory dynamics of inclusion, cannibalization, identity struggle and commodification, in tension